Development of Literacy Teaching Modules in A Book-Based Project at TKIT Syeikh Abdurrauf, Banda Aceh - Fajriah, Dina; Priyanti, Nita (Kirana Publisher (KNPub), 2025)
The improvement of literacy from an early age is one of the main focuses in early childhood education. This study aims to develop a project-based teaching module with a book-based approach to enhance the literacy skills of children at TKIT Syeikh Abdurrauf, Banda Aceh. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). The results indicate that the developed module is effective in increasing children's interest and ability to read, as evidenced by an increase in the evaluation scores of children's early literacy skills. Thus, the book-based project approach is a relevant strategy to support the strengthening of early childhood literacy.